Rapid analysis of country-level mitigation potential from agriculture, forestry and other land uses in Mexico - Sapkota, Tek Bahadur; Ortíz Monasterio, Jose Iván; Sonder, Kai; Wollenberg, Eva Karoline; Richards, Meryl B.; Leyva, Juan Carlos; García, Miguel Angel (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2020)
- Total mitigation potential from the AFOLU sector was the highest in Chiapas (~13 Mt CO2eq) followed by Campeche (~ 8 Mt CO2eq).